GENOTYPIC VARIABILITY AND TRAIT ASSOCIATION IN COTTON (GOSSYPIUM HIRSUTUM L.) SEEDLINGS UNDER NORMAL AND DROUGHT CONDITIONS - KHAN, MF; SHAH, SAS; MANZOOR, T (Biological and Clinical Sciences Research Journal, 2023)
The genetic variability and correlation parameter studies for seedling traits viz; fresh root length, fresh shoot length, fresh shoot weight, dry shoot weight, tissue moisture percentage and root/shoot ratio in 40 accessions of cotton germplasm, including both local and exotic available at different research stations and institutes of Pakistan were carried out under greenhouse in the department of Plant Breeding and Genetics, University of Agriculture, Faisalabad, during the year 2006. Sufficient genetic variability was observed for seedling characters like root length, shoot length, shoot fresh weight, shoot dry weight, tissue moisture percentage and root/shoot ratio under normal and water stress conditions. Based on rooting character and root/shoot ratio, three drought-tolerant cotton genotypes 149-F, BH-124 and DPL-26 and three drought susceptible VH-28, FH-945 and CIM-446 were selected. Correlation coefficients under normal conditions were greater than under drought stress, and the direction of correlations of seedling traits in most cases remained the same. Under normal (r = 0.72) and drought (r = 0.48) conditions, shoot length and root length, were positively correlated, indicating a corresponding increase in shoot length with an increase in root length and vice versa.